Palaemonidae (Crustacea: Decapoda: Caridea) from the shallow waters from Quintana Roo, Mexican Caribbean coast Palaemonidae (Crustacea: Decapoda: Caridea) de las aguas someras de Quintana Roo, Caribe mexicano - Ramiro Román-Contreras; Mario Martínez-Mayén (Revista Mexicana de Biodiversidad, 2010)
Few studies have focused on the palaemonid fauna of the Mexican Caribbean. This study provides a list of shallow water free-living and symbiont shrimps of the family Palaemonidae collected on turtle grass (Thalassia testudinum) in Bahía de la Ascensión, Bahía del Espíritu Santo and Mahahual reef lagoon, Quintana Roo, Mexico. Ten species in 8 genera are reported, of which the genus Periclimenes is the most diverse with 3 species. An updated geographic distribution along the western Atlantic and other regions is provided for all the species. The greatest affinity of the palaemonid fauna studied, besides that with the Caribbean province, is with the Brazilian, Argentinian, and Texan zoogeographic provinces. Of the 10 species reported in this paper, 8 represent new local records in the studied area. Los crustáceos de la familia Palaemonidae del Caribe mexicano han sido poco estudiados. En este trabajo se presenta un listado de palemónidos de vida libre y simbiontes recolectados en el pasto marino Thalassia testudiuim de Bahía de la Ascensión, Bahía del Espíritu Santo y la laguna arrecifal de Mahahual, Quintana Roo, México. Se registran 10 especies pertenecientes a 8 géneros, siendo el género Periclimenes el más diverso con 3 especies. Para todas las especies se proporciona su distribución geográfica en la costa del Atlántico americano así como en otras regiones. Además de la provincia Caribeña, los palemónidos recolectados también muestran alta afinidad con otras provincias zoogeográficas como la Brasileña, Argentina y Texana; de las 10 especies registradas en este estudio, 8 representan nuevo registro local en el área estudiada.